2018
DOI: 10.1088/1748-9326/aaac87
|View full text |Cite
|
Sign up to set email alerts
|

Extreme sea level implications of 1.5 °C, 2.0 °C, and 2.5 °C temperature stabilization targets in the 21st and 22nd centuries

Abstract: Sea-level rise (SLR) is magnifying the frequency and severity of extreme sea levels (ESLs) that can cause coastal flooding. The rate and amount of global mean sea-level (GMSL) rise is a function of the trajectory of global mean surface temperature (GMST). Therefore, temperature stabilization targets (e.g. 1.5• C and 2.0 • C of warming above pre-industrial levels, as from the Paris Agreement) have important implications for coastal flood risk. Here, we assess, in a global network of tide gauges, the differences… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 54 publications
2
120
0
2
Order By: Relevance
“…With 5th to 95th percentiles between brackets. Rasmussen et al () found a similar result with a r 2 of 0.10, which is equivalent to a Pearson correlation coefficient of 0.3. This shows that the simple assumption of a correlation coefficient of 1 made in Church et al () can be refined.…”
Section: Methodsmentioning
confidence: 64%
“…With 5th to 95th percentiles between brackets. Rasmussen et al () found a similar result with a r 2 of 0.10, which is equivalent to a Pearson correlation coefficient of 0.3. This shows that the simple assumption of a correlation coefficient of 1 made in Church et al () can be refined.…”
Section: Methodsmentioning
confidence: 64%
“…We stress that a temporary excursions over 1.5 °C above preindustrial conditions would not necessarily constitute an exceedance of the Paris Agreement, which has been interpreted to refer to human‐induced climate change over periods of at 30 years (Rogelj et al, ). Indeed, complying with the Paris Agreement is still achievable (Rogelj et al, ) and important, given the impact of further warming on Arctic Sea Ice (Jahn, ; Niederdrenk & Notz, ; Sigmond et al, ), Greenland, and West Antarctic ice sheets and sea level rise (Rasmussen et al, ), regional climate (Jacob et al, ; M. A. Taylor et al, ), and extremes (Dosio & Fischer, ; Li et al, ). The first temporary excursions above 1.5 °C, if they occur, would not necessarily lead to many of these effects but they would be an important indication of the proximity to the Paris threshold and could generate interest from the media and general public.…”
Section: Discussionmentioning
confidence: 99%
“…Counts of sea level exceedances per year above a threshold are often assumed to follow a Poisson distribution (e.g., Cid et al, ; Rasmussen et al, ). Maximum likelihood estimates of the Poisson probability mass function that best describe the histograms from the Honolulu threshold experiment show some similarity with the histogram at low values of Δ 99 (Figure b).…”
Section: Methodsmentioning
confidence: 99%